ORTHOGNATHIC SURGERY COMBINED WITH ORTHODONTIC TREATMENT IN A PATIENT WITH BILATERAL CLEFT LIP, PALATE AND ALVEOLUS, WITHOUT ALVEOLAR BONE GRAFT: A CASE REPORT - Siswanto, Yudi; Hutagalung, Magda Rosalina; Sjamsudin, Jusuf; Indri Lakhsmi Putri (Universitas Airlangga, 2018)
Highlights: The orthognathic surgery combined with orthodontic intervention, leads to positive functional and aesthetic outcomes in individuals diagnosed with bilateral cleft lip and palate. It emphasizes the continued importance of adhering to the standard protocol, including alveolar bone grafting before permanent canine eruption, to achieve optimal outcomes. Abstract: Introduction: The incidence of cleft lip and palate is 8 in every 10,000 live births. A patient with this condition experiences a deficiency in maxillary growth. Maxillary hypoplasia leads to malocclusion and skeletal disharmony. Orthognathic surgery at skeletal maturity is the standard procedure at the end of the protocol to correct maxillary hypoplasia resulting in malocclusion not correctable with orthodontics alone. Case Illustration: We report the result of orthognathic surgery performed on a 23 year old male with complete bilateral cleft lip, palate, and alveolus. We proceeded with bimaxillary surgery despite the alveolar cleft. We also recorded a neglected alveolar cleft in which he should have had undergone alveolar bone graft prior to the current procedure. The pre-maxillary segment was stabilized with miniplate followed by Le Fort 1 advancement and mandibular setback guided by an occlusal wafer. Malar augmentation was done by onlay bone grafts. Mandibulo-maxillary fixation was maintained. Postoperatively, a good occlusion and better facial harmony were achieved. He was planned to undergo a septorhinoplasty in the near future. Discussion: Despite adequate treatments following the protocol recommended by many centres, some patients developed some degree of maxillary hypoplasia. A quarter of this population need osteotomies and Le Fort I maxillary osteotomy is the most common procedure to correct retrognathic maxilla. Conclusion: Orthognathic surgery combined with orthodontic treatment in a patient with bilateral cleft lip and palate provided good functional and aesthetic result. However, this procedure cannot replace the standard protocol of having an alveolar.